Pengaruh Problematika Lahan Rawa Lebak pada Minat Keberlanjutan Usahatani Padi di Provinsi Sumatera Selatan - Januarti, Indri; Mulyana, Andy; Yazid, Muhammad; Lifianthi, Lifianthi; Arbi, Muhammad; Damayanthy, Dini; Triyuliani, Maulidia (Universitas Galuh, 2024)
In carrying out rice farming in non tidal swamp land, farmers face various problems. The problems or obstacles faced by farmers cause low productivity and sometimes crop failure. Low productivity has an impact on the low income earned by farming households and in aggregate can disrupt national food security and security. If the income earned by farmers from rice farming continues to decline, it is likely that farmers' interest in cultivating rice will also decrease and over time this will threaten the sustainability of rice farming in non tidal swamp areas. Therefore, this research aims to (1) Analyze the factors that are problematic in non tidal swamp land in rice farming, (2) Analyze indicators of interest in the sustainability of non tidal swamp rice farming in South Sumatra Province and (3) Analyze The influence of the problems of non tidal swamp land on farmers' interest in continuing to cultivate rice in non tidal swamp land. The research method used was a survey method with 80 farmers as respondents. The data analysis used in this research is multiple regression analysis and sustainability index figures. The TKT output target of this research is that the important concepts and characteristics of a technology have been proven analytically and experimentally. The results of the research show that the educational human capital variable has a significant effect on problems in the non tidal swamp area. From the results of the analysis, it can also be seen that the sustainability value is 55, meaning that the sustainability of rice farming in the non tidal swamps of South Sumatra Province is at a fairly sustainable level. These results are also in line with field conditions, where farmers still want or are interested in continuing to carry out rice farming in non tidal swamp land. The relationship obtained from the data analysis carried out between the problems of non tidal swamp land and the interest in sustainable farming which was analyzed using a correlation test had a value of 0.45, which means that there is a fairly strong relationship between the problems of lowland swamp land and farmers' interest in continuing to carry out sustainable farming.